2012
DOI: 10.1002/hpm.2133
|View full text |Cite|
|
Sign up to set email alerts
|

Perceptions of the use of complementary therapy and Siddha medicine among rural patients with HIV/AIDS: a case study from India

Abstract: Allopathic practitioners in India are outnumbered by practitioners of traditional Indian medicine, such as Ayurveda and Siddha. These forms of traditional medicine are currently used by up to two-thirds of its population to help meet primary healthcare needs, particularly in rural areas. Gandeepam is one of the pioneering Siddha clinics in rural Tamil Nadu that is specialized in providing palliative care to HIV/AIDS patients with effective treatment. This article examines and critically discusses the perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…Taken together, we found that the Han nationality, average monthly income, and the time needed to reach the nearest town hospital have significant effects on health care-seeking delay and proved that the accessibility of health services may affect health care-seeking behavior [ 36 , 37 , 38 ]. However, we did not find a strong link between sex, age, and literacy, and treatment delay, somewhat at variance with other studies [ 39 , 40 , 41 , 42 , 43 , 44 ]. It is worth noting that we should strengthen TB control in remote areas, particularly the areas with unsound medical systems.…”
Section: Discussioncontrasting
confidence: 89%
“…Taken together, we found that the Han nationality, average monthly income, and the time needed to reach the nearest town hospital have significant effects on health care-seeking delay and proved that the accessibility of health services may affect health care-seeking behavior [ 36 , 37 , 38 ]. However, we did not find a strong link between sex, age, and literacy, and treatment delay, somewhat at variance with other studies [ 39 , 40 , 41 , 42 , 43 , 44 ]. It is worth noting that we should strengthen TB control in remote areas, particularly the areas with unsound medical systems.…”
Section: Discussioncontrasting
confidence: 89%
“…Users' choices among the diverse systems of medicine show several demographic divides, such as those based on socioeconomic and educational status (Satimia et al 1998;Mazumdar and Gupta 2007), geographical location of practitioners (Satimia et al 1998;Torri 2012) and level of social comfort between the practitioner and patient (Torri 2012), besides the accepted prognosis of the condition (Broom et al 2009), and beliefs about the efficacy of the various systems of medicine for the health condition at hand (Mazumdar and Gupta 2007;Lambert 2012). Thus, more educated, financially better off and Christian villagers in Tanzania reported preferring allopathic medicine to traditional for skin disorders, whereas traditional medicine was the choice of their less educated, economically backward and non-Christian counterparts (Satimia et al 1998).…”
Section: Experiences Of Integrationmentioning
confidence: 99%
“…In contrast, in a study in Mumbai, India, women with higher levels of education were more likely to choose TCAM as their primary recourse for the treatment of gynaecological disorders compared with women with lower levels of education (Mazumdar and Gupta 2007). Siddha clinics for Human Immunodeficiency Virus (HIV) treatment set up in villages in Tamil Nadu were found to be popular for their affordability, and the positive physical health outcomes of the patients, as well as the comfort that the patients felt in interacting with the Siddha practitioners (Torri 2012). Sorsdahl et al (2009) reported, from a systematic review, that people with HIV gravitate towards TCAM practitioners, based on a shared sociocultural background, and the attention given by such practitioners to patients' social and spiritual needs in addition to physical.…”
Section: Experiences Of Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The origins and epistemologies of TCAM variously bear similarities or marked differences with allopathic medicine 40. TCAM systems often overlap and converge with the practices of allopathic practitioners through the incorporation of TCAM practices, including prescription of meditation, diets and physical activity regimen, nutritional supplements and tonics by allopathic practitioners 41…”
Section: Making Sense Of Health Workforce Heterogeneitymentioning
confidence: 99%